Estimation of Stature from Second and Fourth Digit Lengths in Young Adults - Mutluay, Şükriye Deniz; Bozkır, Memduha Gülhal (The Bulletin of Legal Medicine, 2019)
Objectives: Estimating stature from long extremity bones, such as femur, humerus, is commonly usedduring forensic examinations. The aim of this study is to estimate stature by anthropometric measurements of right and left-hands second (2D) and fourth digit (4D) lengths.Method:The sample group consisted of 140 young adults, 70 male and 70 females (aged 21-19 years), whose 2D and 4D lengths were measured (using digital vernier caliper) of their left and right hands. One measurement was taken directly from landmarks from the proximal metacarpophalangeal crease to the finger tips.The program SPSS (Version 17.0) was used to make a descriptive analysis, Student’s t-test was usedto analyze the difference in height 2D and 4D between males and females. One-way ANOVA was usedto determine the potential interactions between anthropometric measurements within each other and stature. Pearson Correlation coefficient and related P values were also used. Statistical significance was assigned to p values
Keywords: digit length; anthropometry; stature estimation